Technical Progress and Induced Innovation in China: A Variable Profit Function Approach - Gary Wong; Belton M. Fleisher; Min Qiang Zhao; William H. McGuire (Institute of Labor Economics (IZA), 2020)
We propose a new methodology to estimate empirically the input price-induced technical change and total factor productivity (TFP) growth in China. Our primary goal is to test Hicks' induced innovation hypothesis by examining whether technical change in China has been induced by sharp increase in input prices that have accompanied its rapid economic growth. Utilizing the idea of a firm's two-stage optimization problem, we develop a new parametric form of the variable profit function wherein the derived input demand and output supply functions can be easily constrained to be regular, and the functional structure is parsimonious in the number of parameters. Applying this methodology to Chinese time series data for 1986–2015, we find that not only is wage-induced innovation significant and quantitatively important, but also that it substantially buffers a long-term decline in TFP growth that would otherwise be quite substantial. We conclude that China's economic growth is predominantly driven by wage-induced innovation along with massive injection of heavily subsidized physical inputs in public works and huge investment in industrial sectors.
Keywords: D22; D24; O30; O53; 330; induced innovation; total factor productivity; variable profit functions; China